Effect of stretch on conduction in myelinated nerve due to wrist movement: An experimental and analytical study - Sabrina Sharmin; Mohammad Abu Sayem Karal; Zaid Bin Mahbub; Khondkar Siddique-e Rabbani (PLoS ONE, 2025)
Based on related measurements by others, an earlier publication suggested increased nerve conduction velocity (NCV) with stretch in myelinated fibers, an anomaly based on existing knowledge, and hypothesized that widening of narrow zigzag gaps between structures of interdigitated Schwann cell processes at the node affected saltatory conduction to produce this increased NCV. A new nodal resistance Rne between the axonal membrane and extracellular fluid was introduced into the century old cable theory. Later, a direct and careful measurement of ulnar NCV across a 10 cm segment around the elbow by another publication appeared to support the suggestion of increased NCV with stretch. However, in order to eliminate the possibility of slacks of ulnar nerve in the upper arm affecting the measurements, the present work was taken up on a shorter 5 cm segment which again supported the suggestion, increasing confidence in the Rne hypothesis. Furthermore, wrist flexion or extension was also observed to affect the ulnar NCV at the elbow to some extent, revealing a new phenomenon. While attempting to formulate an analytical treatment of Rne, the earlier work found it very challenging as the physical structure was extremely complex. Proposing an alternative physical model to simulate the variation in Rne suggested earlier, the current study presents an analytical treatment that relates Rne and a corresponding effective resistivity value to increases in stretch, and relates these quantitatively to stretch values based on the measured values of NCV. This then provided the basis of a quantitative analysis which could be useful for future research. While appreciating that other microstructures in the node at or near the axonal membrane may also contribute to the observed anomaly, but lack of direct experimental evidence related to nerve stretch tends to weigh more on the Rne hypothesis in explaining the anomaly.